1985
DOI: 10.1172/jci111995
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for alteration of the vitamin D-endocrine system in blacks.

Abstract: As compared with values in white subjects, bone mass is known to be increased and urinary calcium to be diminished in black individuals. To evaluate the possibility that these changes are associated with alterations in the vitamin Dendocrine system, an investigation was performed in 12 black subjects, 7 men and 5 women, and 14 white subjects, 8 men and 6 women, ranging in age from 20 to 35 yr. All of them were hospitalized on a metabolic ward and were given a constant daily diet containing 400 mg of calcium, 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
214
1
2

Year Published

1987
1987
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 407 publications
(246 citation statements)
references
References 21 publications
(15 reference statements)
26
214
1
2
Order By: Relevance
“…Several studies have shown that black individuals may have higher PTH levels and also larger parathyroid glands than white individuals, and similar findings have been reported among patients with ESRD (15)(16)(17)(18)(19)(20)(21)(22). These findings cannot be entirely explained by differences in calcium intake and vitamin D status, and the possibility that skeletal resistance to PTH may be partly responsible has been suggested (23)(24)(25).…”
Section: Discussionmentioning
confidence: 54%
“…Several studies have shown that black individuals may have higher PTH levels and also larger parathyroid glands than white individuals, and similar findings have been reported among patients with ESRD (15)(16)(17)(18)(19)(20)(21)(22). These findings cannot be entirely explained by differences in calcium intake and vitamin D status, and the possibility that skeletal resistance to PTH may be partly responsible has been suggested (23)(24)(25).…”
Section: Discussionmentioning
confidence: 54%
“…Along these lines, it is of possible significance that the vitamin D 25-hydroxylase-deficient subject identified here was Nigerian. Individuals with dark skin require exposure to sunlight for longer periods of time to generate requisite levels of vitamin D 3 as compared with those with less skin pigmentation and may be more sensitive to impaired synthesis of the vitamin (43)(44)(45)(46). Furthermore, we sequenced exon 2 of the CYP2R1 gene in 50 control subjects from Nigeria (22), and identified one individual who was heterozygous for the L99P mutation.…”
Section: -40)mentioning
confidence: 99%
“…The key element in our hypothesis is the increased responsiveness of specific target tissues of hypertensive individuals to agonists exerting their cellular effect through the Ca 2+ messenger system and the Na 80 Moreover, hypertensive blacks exhibit a further increase in PTH levels with a high salt intake. 81 These observations suggest that salt sensitivity in blacks may relate to different cellular regulation of Na + and Caj 2+ .…”
mentioning
confidence: 99%